Implementasi Pembelajaran Fikih melalui Kitab Diyanah: Tinjauan Behavioristik, Konstruktivistik, dan Pendidikan Islam pada Materi Najis - Feby Angelina Putri; Hosniati; Endah Tri Wisudaningsih (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to describe the implementation of Fiqh learning on the topic of najis (impurity) through the Kitab Diyanah at SD Unggulan Cahaya Cendekia and to analyze the supporting factors, inhibiting factors, and the impact of its application on students’ understanding and behavior. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with the principal, Fiqh teacher, and students, as well as documentation of learning activities. The data were analyzed descriptively using qualitative methods with source triangulation to ensure data validity. The results of the study indicate that Fiqh learning through the Kitab Diyanah is carried out using methods such as reading nadzom (rhythmic verses), translation, explanation of meaning, and practical activities. The teacher acts as a facilitator who guides students to understand the concept of najis contextually and applicatively. Supporting factors include teacher competence, a religious school environment, and a curriculum that emphasizes moral values. Meanwhile, inhibiting factors consist of limited learning time and students’ difficulty in understanding Arabic terms in the book. The implementation of the Kitab Diyanah has proven effective in improving students’ understanding of Islamic jurisprudence regarding najis and encouraging cleanliness and purity in daily life. This learning model also strengthens students’ Islamic character through the habituation of clean behavior and respect for religious values. Theoretically, the findings of this study align with the behaviorist theory (Skinner), constructivist theory (Vygotsky), and Islamic education theory, which emphasize the integration of knowledge, practice, and morality.